Influencer Marketing Credibility And Its Effect On Purchase Intention In Social Media Platforms - Lestari, Utami Puji; Gusti, Yenni Kurnia; Mere, Klemens; Amanda, Mabella (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
The rapid development of digital technology has transformed marketing communication, particularly through the use of social media platforms such as Instagram, TikTok, and YouTube. One of the most widely adopted strategies in digital marketing is influencer marketing, where influencers promote products or services to their followers. This study aims to analyze the influence of influencer marketing credibility on consumer purchase intention in social media environments through a literature review approach. The research applies a systematic literature review (SLR) method by examining previous empirical studies published in reputable academic databases. The findings indicate that influencer credibility—primarily reflected through expertise, trustworthiness, and attractiveness—plays a crucial role in shaping consumer perceptions and influencing purchasing decisions. Influencers who are perceived as knowledgeable, authentic, and relatable tend to build stronger trust among followers, which subsequently increases their willingness to purchase recommended products. Additionally, the interactive nature of social media platforms strengthens the relationship between influencers and audiences, further enhancing the effectiveness of marketing messages. The study concludes that influencer credibility is a key determinant of successful influencer marketing strategies and provides important implications for businesses seeking to improve consumer engagement and purchase intention in digital marketing contexts.